Online Banking Service Quality and E-customer Loyalty: The Mediating Role of E-customer Satisfaction in Commercial Bank in Butwal Sub-Metropolitan City (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to examine the impact of e-customer satisfaction on the relationship between e-customer loyalty and the quality of online banking services in commercial banks.Methods: A modified questionnaire using a seven-point Likert scale was used to gather data from 400 clients for the study. Of those, 384 complete responses were acquired, yielding a 96% response rate. Regression analysis, correlation, parametric and non-parametric tests, and the independent sample t-test were among the statistical methods used in this descriptive and causal-comparative study design.Results: The results indicate that the organization’s website and security/privacy are the primary factors influencing e-customer loyalty. Additionally, e-customer satisfaction plays a significant mediating role in the relationship between the organization’s website, user-friendliness, and e-customer loyalty. Moreover, the study reveals that e-customer satisfaction serves as a partial mediator in the connection between security/privacy and e-customer loyalty.Conclusion: Based on the results of study, commercial banks should focus on enhancing security and privacy measures on their online banking platforms to strengthen e-customer loyalty.